2004
DOI: 10.1123/ijsnem.14.2.236
|View full text |Cite
|
Sign up to set email alerts
|

Cordyceps Sinensis (CordyMax Cs-4) Supplementation Does Not Improve Endurance Exercise Performance

Abstract: It is purported that supplementation with Cordyceps Sinensis (CordyMax Cs-4) will improve oxidative capacity and endurance performance. The intent of this investigation was to examine the effects of CordyMax Cs-4 supplementation on VO<(2peak,) ventilatory threshold, and endurance performance in endurance-trained cyclists. Twenty-two male cyclists participated in 5 weeks of supplementation with CordyMax Cs-4 tablets (3 g/d). Training intensity was maintained by weekly documentation and reporting throughout the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
26
0
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(28 citation statements)
references
References 12 publications
1
26
0
1
Order By: Relevance
“…One study has demonstrated improvements in VO 2 max in sedentary men [79] with relatively high doses (4.5 g/d for 6 weeks) of cordyceps. However, with lower doses (2.5 g) similar to what is found in GT in the present study, there were no ergogenic effects of cordyceps reported in previous studies on VO 2 max [81-83] in healthy, active men. Thus, given the conflicting evidence, cordyceps may be another ingredient in GT that acted synergistically to improve CV and training volume in the present study.…”
Section: Discussionsupporting
confidence: 78%
“…One study has demonstrated improvements in VO 2 max in sedentary men [79] with relatively high doses (4.5 g/d for 6 weeks) of cordyceps. However, with lower doses (2.5 g) similar to what is found in GT in the present study, there were no ergogenic effects of cordyceps reported in previous studies on VO 2 max [81-83] in healthy, active men. Thus, given the conflicting evidence, cordyceps may be another ingredient in GT that acted synergistically to improve CV and training volume in the present study.…”
Section: Discussionsupporting
confidence: 78%
“…This observed effect may be due to the presence of carbohydrates (45-51% of dry weight) and polysaccharides (210KD 9 ) in the Indian isolate of Cordyceps sinensis , which has been earlier reported to promote endurance and energy metabolism (Manabe et al, 2000;Li and Li, 2009). In contrary, a number of human studies using trained cyclists have also reported the inefficiency of CS and CS-based commercial supplements (Earnest et al, 2004;Parcell et al, 2004;Colson et al, 2005;Herda et al, 2008) in improving performance. However, these studies have been conducted with athletes who have attained their maximum metabolic and ventilatory response and the scope of endurance improvement is minimal.…”
Section: Discussionmentioning
confidence: 98%
“…The proposed reasons for the observed increased energy output by CS supplementation are stabilization of blood sugar metabolism and increased ATP production. But an equivocal number of studies have also reported ineffectiveness of CS and CS-based energy supplements in increasing the exercise capacity in competitive cyclists (Parcell et al, 2004;Earnest et al, 2004;Colson et al, 2005). Irrespective of these reports, molecular studies assessing the effectiveness of CS supplementation on skeletal muscle metabolic programme and resulting effects on exercise endurance is lacking.…”
Section: Introductionmentioning
confidence: 99%
“…When combined with three weeks of high intensity interval training, a pre-workout blend containing cordyceps sinensis had positive effects on critical velocity, an aerobic performance measure (Smith, Fukuda, Kendall, & Stout, 2010). Despite potential benefits, a number of studies have found no benefits of cordyceps supplementation on aerobic and anaerobic performance (Colson et al, 2005; Earnest et al, 2004; Parcell, Smith, Schulthies, Myrer, & Fellingham, 2004). To date, research on the ergogenic effects of cordyceps is limited and inconclusive as to its benefits to exercise.…”
Section: Introductionmentioning
confidence: 99%